PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE LEARNING TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVB SDN 024 TARAI BANGUN KECAMATAN TAMBANG - Citra, Rizka Yulia; Marhadi, Hendri; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is held because of a lowstudents learning result of IPS subject of students of class IVB SDN 024 Tarai Bangun. From 46 students there are 21 students that achieve the KKM (45,65%) there are 25 students that did not achieve the KKM yet (54,35%) with the average of 70,86. The purpose of this research is to increas the learning result of IPS subject of student of class IVB SDN 024 Tarai Bangun with the implementation of Learning Together learning model. The analysis of research result the basic score of students learning result of IPS subject has increased in cycle I and II from 70,86 increased by 75.21 and increased again by 80,54. The completeness of students learning result of IPS subject also increased from students basic score 45,65% (not complete) increased by 78,26% (not complete), in cycle I and cycle II and increased again by 84,48% (complete). The percentage of teacher’s activity after the implementasion of Learning Together learning model in the first meeting by 66,87% with good category. In the second meeting of first cycle the percentage increased become 70,83% with good category. In the first meeting of cycle II the percentage of teacher’s activity has increased again become 87,5% with very good category. In the second meeting of cycle II the percentage of teacher’s activity has increased again become 91,67% with very good category. The percentage of students activity in the fist meeting 62,5% with good category. In the second meeting of cycle I percentage of students activity has increased again become 66,87% with good category. In the first meeting of cycle II the percentage of students activity has increased again become 79,17% with good category, in the second meeting of cycle II the percentage of students activity has increased again become 87,5% with very good category. We can conclude that the implementation of of Learning Together type of cooperatif learning can increase the students learning result of IPS subject of students of class IVB SDN 024 Tarai Bangun.Keyword: Learning Together, IPS subject learning result.